Automated lighting : the art and science of moving light in theatre, live performance, broadcast, and entertainment - Cadena, Richard (Focal Press, 2006)
""Automated Lighting-Technology, Applications, and Design"" is a comprehensive text covering everything you will need to know as a working or aspiring lighting professional about automated lighting fixtures, systems, how they are used and design issues you will face. It is written in clear, easy-to-understand language but includes enough detailed information that the most experienced technician and engineer will appreciate and benefit from reading. Subjects covered include the history of automated lighting, DC and AC electricity, basic electronics, power supplies, digital electronics, electro-